Synthesis and application of highly ordered arrays of TiO2 rods grown on electrospun PVDF fibers. (25th July 2017) - Zhang, Zhi-Guang; Liu, Hui; Zhang, Bin; Zhang, Jun; Liu, Rong-Zhan; Ning, Xin; Long, Yun-Ze
Abstract: This paper reports the controlled synthesis of highly ordered arrays of rutile TiO2 rods with tunable size and properties on electrospun PVDF Fibers by using a low-temperature hydrothermal growth strategy. Well-defined, highly ordered, vertically oriented TiO2 rod arrays covering on the PVDF fibers backbone were obtained. In order to study the morphology-dependent optical and photocatalytic properties of the hierarchical composites, the hydrothermal treatment time was varied, resulting in rime-like (6 h) and rod bundles (4 h and 10 h) morphologies. By contrast, the crystallinity, grain size and optical properties of the sample depended on the hydrothermal treatment time. After being irradiated for 600 min with an 18 W UV lamp, the photocatalytic efficiency of rhodamine B for the sample hydrothermal treated for 4 h, 6 h and 10 h was about 28%, 37% and 85%, respectively. A slight decrease in the photodegradation efficiency can be detected after five times recycled experiments. Moreover, further study indicates that the rime-like branched structure promote photocatalytic efficiency.